Utilization of Soil Amandment to Optimize Growth and Yield of Pakcoy (Brassica rapa l.) on Degraded Soil - Nurfadilah, Ayu; Handayani, Dila; Eviyati, R; Atmaja, Ida Setya Wahyu (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2024)
Slurry is by product of stone process, as cutting and polishing of natural stone. The consequence of the exixtence of slurry can be seen on irrigation water quality and degraded soil such sufficient nutrient and soil physics properties. The aims of this research was to analyse the effect of soil amandment on degraded soil to improve growth of Pakcoy (Brassica rapa L.). This research was conducted in June to August 2024 in Dukuhpuntang Cirebon using the Completely Randomized Design (CRD). The treatments are combination of the rice straw compost and soil affected by natural stone waste as planting media, including: A0 (control 100% soil affected by natural stone waste), A1 (25% soil affected by natural stone waste: 75% rice straw compost), A2 (50% soil affected by natural stone waste: 50% rice straw compost), A3 (75% soil affected by natural stone waste: 25% rice straw compost). Each combination treatment repeated 6 times. The research show that the utilization of rice straw compost in soil affected by natural stone waste as planting media increasing number of plant height, number of leaves, and fresh weight consumption by 41%, 39%, and 83%. Soil amendment improving the soil properties through ideal condition for plant growth, including reducing the soil compaction.